2020
DOI: 10.2196/16066
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Virtual Reality Biofeedback Game (DEEP) to Reduce Anxiety and Disruptive Classroom Behavior: Single-Case Study

Abstract: Background Many adolescents in special education are affected by anxiety in addition to their behavioral problems. Anxiety leads to substantial long-term problems and may underlie disruptive behaviors in the classroom as a result of the individual’s inability to tolerate anxiety-provoking situations. Thus, interventions in special needs schools that help adolescents cope with anxiety and, in turn, diminish disruptive classroom behaviors are needed. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 72 publications
2
65
0
5
Order By: Relevance
“…Another contribution of this adolescent-specific review is the identification of several gaps in the literature for this population. The studies included in this review focused on pain and pain-related anxiety, however, recent studies in nonhospital settings have shown great potential for VR to be used to reduce other kinds of psychological distress in adolescents in a range of circumstances [78][79][80][81][82]. Emergency departments are a hospital environment that adolescents are more likely to use than other age groups [83], but also one that adolescents find particularly distressing due to long waits, loud sounds, bright lights, privacy intrusions, and exposure to the distress of others [84].…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…Another contribution of this adolescent-specific review is the identification of several gaps in the literature for this population. The studies included in this review focused on pain and pain-related anxiety, however, recent studies in nonhospital settings have shown great potential for VR to be used to reduce other kinds of psychological distress in adolescents in a range of circumstances [78][79][80][81][82]. Emergency departments are a hospital environment that adolescents are more likely to use than other age groups [83], but also one that adolescents find particularly distressing due to long waits, loud sounds, bright lights, privacy intrusions, and exposure to the distress of others [84].…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…Another example is DEEP, an applied game that teaches diaphragmatic breathing in a gamified VR-environment via biofeedback. Although the effect was small, after using DEEP, anxiety was reduced in children in special education ( 52 ). These types of engaging, experience-based approaches might also be a good fit for enhancing relaxation skills in the often unmotivated forensic psychiatric patient populations ( 44 ).…”
Section: Ehealth and The Need Principlementioning
confidence: 99%
“…This type of game is often defined in the literature as a “serious game” [ 69 ], as gaming features are used as the primary medium for serious purposes [ 66 ]. Several custom-made video games for relaxation integrate biofeedback techniques into the game modes, such as Deep [ 70 , 71 ], Nevermind [ 72 ], MindLight [ 73 , 74 ], Dojo [ 75 , 76 ], and StressJam [ 77 ]. Furthermore, studies have shown that ad hoc video games could help adults with anxiety better handle emotional and physiological responses to stressors [ 78 ] and improve behavioral performance on anxiety-related stress tasks [ 79 ].…”
Section: Introductionmentioning
confidence: 99%